Peran Greenpeace Indonesia dalam Melindungi Lembah Grime Nawa dari Deforestasi di Papua - Rahman, Bimo Agung Wibowo; Karjaya, Lalu Puttrawandi; Dewanto, Pamungkas Ayudaning; Estriani, Heavy Nala (Indonesian Journal of Peace and Security Studies (IJPSS), 2023)
This article aims to analyze the role of Greenpeace Indonesia in saving the Grime Nawa Valley from deforestation in Papua. Although President Joko Widodo and several government agencies have revoked PNM LLC, to date, the impact of the operations of PNM LLC, namely deforestation in the Grime Nawa Valley, is still unresolved. This was known by Greenpeace Indonesia because the organization did not ignore its observations and discovered through satellite imagery that PT. PNM is still operating. This issue becomes the focal point of this article to analyze thoroughly. This research uses the concept of NGOs and deforestation with descriptive qualitative research methods. The usage of Greenpeace Indonesia, under the concept of NGO, will help reveal the roles it carries, namely advocacy, monitoring, facilitator and consultation. It is hoped that Greenpeace Indonesia and the community can stop PNM LLC’s business by carrying out its role. The research results show that Greenpeace Indonesia has carried out its role with various results, some of which are in its advocacy role, Greenpeace Indonesia carried out a campaign to save the Grime Nawa Valley. The role of monitoring is to go to the field to see the impacts caused. The role of the facilitator is to organize the traditional community of the Grime Nawa Valley. The final role of consultation is to open the door to discussion regarding problems in the Grime Nawa Valley. After fulfilling its roles, Greenpeace Indonesia successfully reduced the impact of PNM LLC’s operations in the Grime Nawa Valley